The European & Developing Countries Clinical Trials Partnership (EDCTP) Knowledge Hub: developing an open platform for facilitating high-quality clinical research - Driver, S; Gray, S; Sikhondze, W; Awuonda, K; Wilcox, H; Segrt, A; Pandya, L; Roth, J; Makanga, M; Lang, T (BioMed Central, 2022)
There is stark global inequity in health research in terms of where studies happen, who leads the research and the ultimate beneficiaries of the results generated. Despite significant efforts made, limited research ideas are conceptualised and implemented in low-resource settings to tackle diseases of poverty, and this is especially true in sub-Saharan Africa. There is strong evidence to show that the barriers to locally led research do not vary largely between disease, study type and location and can be largely solved by addressing these common gaps. The European & Developing Countries Clinical Trials Partnership (EDCTP) was established in 2003 as a European response to the global health crisis caused by the three main poverty-related diseases HIV, tuberculosis and malaria. EDCTP has established a model of long-term sustainable capacity development integrated into clinical trials which addresses this lack of locally led research in sub-Saharan Africa, supporting the development of individual and institutional capacity and research outputs that change the management, prevention and treatment of poverty-related and neglected infectious diseases across Africa. In recognition of emergent data on what the barriers and enablers are to long-term, sustainable capabilities to run studies, EDCTP formed a new collaboration with The Global Health Network (TGHN) in September 2017, with the aim to make a set of cross-cutting tools and resources to support the planning, writing and delivery of high-quality clinical trials available to research staff wherever they are in the world, especially those in low- and middle-income countries (LMICs) via TGHN platform. These new resources developed on the 'EDCTP Knowledge Hub' are those identified in the mixed method study described in this commentary as being key to addressing the gaps that the research community report as the most limiting elements in their ability to design and implement studies. The Knowledge Hub aims to make these tools freely available to any potential health research team in need of support and guidance in designing and running their own studies, particularly in low-resource settings. The purpose is to provide open access to the specific guidance, information and tools these teams cannot otherwise access freely. Ultimately, this will enable them to design and lead their own high-quality studies addressing local priorities with global alignment, generating new data that can change health outcomes in their communities.